2014
DOI: 10.1155/2014/763563
|View full text |Cite
|
Sign up to set email alerts
|

Finger Length Ratios in Serbian Transsexuals

Abstract: Atypical prenatal hormone exposure could be a factor in the development of transsexualism. There is evidence that the 2nd and 4th digit ratio (2D : 4D) associates negatively with prenatal testosterone and positively with estrogens. The aim was to assess the difference in 2D : 4D between female to male transsexuals (FMT) and male to female transsexuals (MFT) and controls. We examined 42 MFT, 38 FMT, and 45 control males and 48 control females. Precise measurements were made by X-rays at the ventral surface of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Given the observed homogeneity for results in transwomen, it seems plausible that these additional data would not change the overall picture in this group. More importantly, the discussions of the relevant reports suggest that the observed effects were in line with expectations (Veale, Clarke, & Lomax, 2010;Vujović et al, 2014). We therefore think it is fair to conclude that inclusion of these effects would not have substantially changed our findings.…”
Section: Natal Females Leō Handsupporting
confidence: 69%
“…Given the observed homogeneity for results in transwomen, it seems plausible that these additional data would not change the overall picture in this group. More importantly, the discussions of the relevant reports suggest that the observed effects were in line with expectations (Veale, Clarke, & Lomax, 2010;Vujović et al, 2014). We therefore think it is fair to conclude that inclusion of these effects would not have substantially changed our findings.…”
Section: Natal Females Leō Handsupporting
confidence: 69%
“…While this Male GD lower 2D:4D in both hands; female GD lower in right hand. Vujović et al (2014) 38 transmen Lower 2D:4D than controls.…”
Section: Gender Dysphoria and Key Hypothesesmentioning
confidence: 76%
“…We repeated the search once more using 2D:4D AND 'gender dysphoria'. This gave us 100 results of which one was both new and relevant (Vujović et al, 2014). We also checked the reference lists of articles within our inclusion criteria, but no further germane studies were revealed.…”
Section: Gender Dysphoria and 2d:4d Ratiomentioning
confidence: 99%
“…Our study which was conducted in central Indian population included only left hand of the sampled 92 subjects and it showed no statistically significant difference in the 2D:4D ratios of male and female. This can be attributed to the fact that a different population group was studied and the hypothesis by some of the studies that right hand tends to show more significant ratio difference than left hand [18].…”
Section: Research Articlementioning
confidence: 99%